On the indian and his introduction into the United States army - Bridgman, Judd Noble (My University, 1891)
Introduction: That a solution of the “Indian Question” whereby the Indian race may be questioned must come quickly few will question. That the Indian has received nothing but abuse and cruelty from the hands of the whites many doubt, but that this is a fact those who are most acquainted with the question will not attempt to deny. This subject is of peculiar importance as it affects the well-being of a nation and a race; it is of interest as it throws light or shadow upon the history of a world. Its solution may save a nation from disgrace, it may save a race from extinction, or it may do neither. The average American looks at it only as a matter of dollars and cents and the only thought he gives it is to how he can extort the most from his unlucky victim. The continuance of the present policy will soon solve the problem by leaving only the forces of this once proud race to bleach upon the hillsides of their former houses.
The indian, and his introduction into the United States army
Citation: Bridgman, Judd Noble. On the indian and his introduction into the United States army. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Army; Native American; Assimilation; Racism; History; Abuse; Theses; Manuscripts (documents)